Cobimetinib alone and plus venetoclax with/without atezolizumab in patients with relapsed/refractory multiple myeloma - Schjesvold, Fredrik; Paiva, Bruno; Ribrag, Vincent; Rodriguez-Otero, Paula; San-Miguel, Jesus F.; Robak, Pawel; Hansson, Markus; Onishi, Maika; Hamidi, Habib; Malhi, Vikram; Dail, Monique; Javery, Apurva; et al. (Clinical lymphoma, myeloma & leukemia, 2023)
Mitogen-activated protein kinase pathway mutations are present in >50% of patients with relapsed/refractory (R/R) multiple myeloma (MM). MEK inhibitors show limited single-agent activity in R/R MM; combination with B-cell lymphoma-2 (BCL-2) and programmed death-ligand 1 inhibition may improve efficacy. This phase Ib/II trial (NCT03312530) evaluated safety and efficacy of cobimetinib (cobi) alone and in combination with venetoclax (ven) with/without atezolizumab (atezo) in patients with R/R MM.